ESTIMATING MATERNAL OBSTETRIC RISK; THE APPLICATION OF SURVIVAL ANALYSIS TECHNIQUES - Luguterah, Albert (European Scientific Journal, ESJ, 2015)
Studies on Maternal Survival and its converse mortality are of much recent origins with basic statistics, including data, in this area still a major challenge particularly for developing countries. While there are several estimators of maternal mortality and hence survival, the development of an appropriate measure of obstetric risk has been a challenge. In this study, the application of survival analysis techniques in developing appropriate estimates for maternal mortality and its usefulness have been proposed. Results of its application to data from Ghana showed that while about 92 % of pregnant women made it alive to delivery, only 83% of them survived to the end of the postpartum period. There were significant differentials by location, Obstetric history and Maternal Age: The Weibull distribution described maternal survival well.